2022
DOI: 10.1016/j.omto.2021.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic measles vaccines encoding PD-1 and PD-L1 checkpoint blocking antibodies to increase tumor-specific T cell memory

Abstract: PD-1/PD-L1 checkpoint blockade has achieved unprecedented success in cancer immunotherapy. Nevertheless, many immune-excluded tumors are resistant to therapy. Combination with oncolytic virotherapy may overcome resistance by inducing acute inflammation, immune cell recruitment, and remodeling of the tumor immune environment. Here, we assessed the combination of oncolytic measles vaccine (MV) vectors and PD-1/PD-L1 blockade. In the MC38cea model of measles virus oncolysis, MV combined with anti-PD-1 and MV vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
(83 reference statements)
1
12
0
Order By: Relevance
“…Of note, expression of programmed death ligand-1 (PDL-1) was found in CDV-infected lungs by transcriptome analysis (cluster 1) in the present study, which acts as negative regulator of T cell effector responses and IL-2 transcription [ 116 , 117 ]. Interestingly, blockage of the programmed cell death-1/PDL-1 checkpoint pathway by measles virus enhances effector memory T cell response in vitro and in mouse models, representing a potential target for immunotherapy [ 118 , 119 , 120 ]. Noteworthy, immunomodulatory cytokines such as IL-4, IL-10 and TGF-β showed no significant changes in CDV-infected lung tissue in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, expression of programmed death ligand-1 (PDL-1) was found in CDV-infected lungs by transcriptome analysis (cluster 1) in the present study, which acts as negative regulator of T cell effector responses and IL-2 transcription [ 116 , 117 ]. Interestingly, blockage of the programmed cell death-1/PDL-1 checkpoint pathway by measles virus enhances effector memory T cell response in vitro and in mouse models, representing a potential target for immunotherapy [ 118 , 119 , 120 ]. Noteworthy, immunomodulatory cytokines such as IL-4, IL-10 and TGF-β showed no significant changes in CDV-infected lung tissue in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously reported efficacy of MV and ICB combination therapy in immunocompetent mouse models of melanoma, colorectal cancer, and glioblastoma ( 6 10 ). These studies showed delayed tumor progression and prolonged survival, an increased intratumoral T cell infiltration, an increased ratio of effector to regulatory T cells, and enhancement of tumor-specific T cell responses upon MV and ICB combination treatment.…”
Section: Introductionmentioning
confidence: 88%
“…[151] Recently, an interesting study revealed that combination therapy using oncolytic measles vaccine (MV) vectors encoding anti-PD-1 or anti-PD-L1 genes and PD-1/PD-L1 blockers leads to a slight increase in survival and intratumoral IFN-γ compared with monotherapy by control MV or anti-PD-1/PD-L1 antibodies. [152] Therefore, combining oncolytic viruses encoding cytokine genes (TNF-α, IL-2, IL-12, IFN-γ) with anti-PD-1/PD-L1 antibodies can be more effective in the treatment than anti-PD-1 or anti-PD-L1 encoding MVs and anti-PD-1/PD-L1 antibodies. A thymidine kinase (TK) gene deleted oncolytic vaccinia virus (ΔTK-Armed-VACV) encoding anti-PD-1, and anti-4-1BB (CD137) antibody genes were designed to treat cancer.…”
Section: Anti Pd-1 and Anti Pd-l1 Antibodiesmentioning
confidence: 99%